Investigating Figurative Language Usages and the Dictions on the Instagram Platform - Isnaini, Nur Alfiana (English Department, Faculty of Humanities, Andalas University, 2023)
This research aims to understand about the different usages of figurative language, the dictions on the Instagram platform and how both of those terms are used. However, the object of this research are two selected accounts that fit to this research, those are @moodcewekk and @test-psikologi. This research also applied the descriptive-qualitative research, because the data has been analyzed by describing the results and its forms are written text. Besides, the theory that used in this research is the sociolinguistic theory. Meanwhile, the way the researcher collected the data is through capturing the captions (screen shoot). Then, for data analysis, the writer used the annotating and heeding method to get differences of the data. Therefore, after doing the analysis towards the data, the researcher found the results of this research are personification which has two kinds, both of them are using complete sentences and other used subject and predicate only. For hyperbole, it has several usages, such as the prohibition, the declarative or statements, and the advices. Then, for metaphor, it contains of direct and indirect sentence. Besides, for Hypernym-Hyponym, @moodcewekk is less using the dictions than @test-psikologi. Finally, the polysemy can be categorized as noun, verbs and adjective.